Small renal cell carcinoma presented with pleural metastasis and multiple bone metastasis ; a case report - Ohara, Mizuho (Hinyokika kiyo. Acta urologica Japonica, 2011)
The patient is a 69-year-old male. His chief complaint was chest pain. Because imaging studies suggested pleural mesothelioma associated with multiple bone metastases, right pleural tumor resection was performed. Pathological diagnosis was metastatic pleural tumor, and renal cell carcinoma (RCC) was suspected as its origin. Dynamic computed tomography showed a small tumor in the right kidney. The tumor was 15 mm in diameter and consistent with RCC. Laparoscopic radical nephrectomy was performed for the right kidney. Pathological diagnosis was RCC, clear cell carcinoma with sarcomatoid component, T1aN0M1, stage IV. Sorafenib therapy was started 46 days after the operation as a systemic therapy, and stable disease has been maintained. Generally, small RCC is assumed to have a good prognosis. However, a small percentage of patients with small RCC have distant metastasis at the time of diagnosis, and the prognosis is reported to be poor. We report this case, and a review of the literature